Analysis of the mechanical behaviors of nonmetallic un-bonded flexible pipe under different loads - Yu, Jin; You, Xuegang; Kong, Tianwei; Xia, Mengying; Lv, Ruhong; Zhang, Kezheng; Wang, Baodong (Frontiers in Materials, 2025)
The growing demand for lightweight, corrosion-resistant, and cost-effective solutions in offshore oil and gas operations has driven the transition from traditional metallic pipes to advanced non-metallic flexible pipes. A rigorous three-dimensional nonlinear finite element model was developed using ABAQUS/Explicit, incorporating actual material parameters, structural nonlinearity, and interlayer contact behavior. The model was validated through full-scale burst pressure tests, demonstrating excellent agreement (within 13.4% error) with experimental results. Key findings indicate that internal pressure of 35 MPa can increase tensile stiffness by up to 22.1%, while external pressure of 15 MPa enhances it by 8.9%. Under combined axial tension-bending loading conditions, the flexible pipe demonstrates higher bending stiffness compared to single-load scenarios. Internal pressure exhibits minimal influence on non-slip bending stiffness but simultaneously elevates both critical slip curvature and post-slip stiffness. In contrast, external pressure significantly improves both critical slip curvature and post-slip stiffness. These quantitative results provide crucial design guidelines for performance optimization of non-metallic pipes in deepwater applications.